2010
DOI: 10.1029/2009jd011780
|View full text |Cite
|
Sign up to set email alerts
|

Joint retrieval of surface reflectance and aerosol optical depth from MSG/SEVIRI observations with an optimal estimation approach: 2. Implementation and evaluation

Abstract: An original method, based on optimal estimation, was presented in a part one of this paper for the joint retrieval of the mean daily total column aerosol optical depth and the surface Bidirectional Reflectance Factor (BRF) from the daily accumulated Meteosat Second Generation–Spinning Enhanced Visible and Infrared Imager (MSG/SEVIRI) observations in the solar channels. The objective of this paper is to evaluate the benefits of the proposed approach and to document the limits of the algorithm assumptions in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…This choice of an appropriate aerosol model plays a significant part in the retrieval of aerosols from satellites. An additional large source of uncertainty comes from the assumptions on surface albedo (Thomas et al, 2009;Govaerts et al, 2010;Wagner et al, 2010). This aspect will not be studied in the current paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice of an appropriate aerosol model plays a significant part in the retrieval of aerosols from satellites. An additional large source of uncertainty comes from the assumptions on surface albedo (Thomas et al, 2009;Govaerts et al, 2010;Wagner et al, 2010). This aspect will not be studied in the current paper.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric aerosols have been monitored for years from several satellite instruments including the Ozone Monitoring Instrument (OMI) (Torres et al, 2007), the Moderate Resolution Imaging Spectroradiometer (MODIS) van Donkelaar et al, 2013), the Global Ozone Monitoring Experiment-2 (GOME-2), the Multi-angle Imaging SpectroRadiometer (MISR) , the (Advanced) Along-Track Scanning Radiometers ((A)ATSR) (Thomas et al, 2009;Sayer et al, 2010Sayer et al, , 2012, the Cloud-Aerosol Lidar and Infrared Path finder (CALIPSO), the Scanning Imaging Absorption spectroMeter for Atmospheric Chartography (SCIAMACHY), the Polarisation and Directionality of the Earth's Reflectances (POLDER) (Dubovik et al, 2011) and the Spinning Enhanced Visible and Infrared Imager (SE-VIRI) Wagner et al, 2010). The instruments vary in terms of spatial and spectral resolution, polarisation, and viewing geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, two-channel retrievals were performed (Mishchenko et al 1999;Ignatov et al 2004), adding the 0.85 micrometer band, refining the assumed ocean surface reflectance model, and also retrieving the Angstrom exponent (ANG, related to the spectral slope of AOD), a quantity that can provide some indication of particle size. Similarly, AOD retrieval algorithms have been developed for imagers aboard geostationary satellites, such as NOAA's GOES series (Knapp 2002) and European Space Agency's Spinning Enhanced Visible and Infrared Imager (SEVIRI; Popp et al 2007;Wagner et al 2010), providing high-temporal-resolution products as frequently as every 15 or 30 min, making it possible to at least qualitatively map the development of aerosol plumes. Although broad spectral bands and poor radiometric calibration limit the quantitative application of these data, early results demonstrated the long-range, over-ocean transport of dust, smoke, and pollution particles from terrestrial sources (e.g., Husar et al 1997), highlighting the need to consider aerosol effects on the global energy budget.…”
Section: Early Aerosol Optical Depth (Aod) Measurementsmentioning
confidence: 99%
“…Tech., 4, 2543Tech., 4, -2565Tech., 4, , 2011 www.atmos-meas-tech.net/4/2543/2011/ corrected from radiometric and geometric non-linearity, geolocated and calibrated (Muller, 2007). Recent investigations have used the Spinning Enhanced Visible and InfraRed Imager (SEVIRI) sensor onboard MSG to retrieve AOT over land in the visible channel centred at 0.6 µm and noted VIS06 in the following (Popp et al, 2007;Guerrieri et al, 2007;Carrer et al, 2010;Wagner et al, 2010). All these studies showed the feasibility of retrieving the AOT at time-scales ranging from 15 min (Popp et al, 2007;Guerrieri et al, 2007) to daily means (Carrer et al, 2010;Govaerts et al, 2010;Wagner et al, 2010).…”
mentioning
confidence: 99%